Neuroimmunoendocrinal markers of prediction of preeclampsia - D. Ye. Barkovsky (Zaporozhye State Medical University, 2018)
Objective: to establish the features of neuroendocrine regulation of homeostasis and the immune system of a woman in the 1 st trimester of pregnancy complicated by preeclampsia, and to establish prognostic criteria for the occurrence of this obstetric complication. Materials and methods. A dynamic observation of the course of pregnancy, childbirth and the postpartum period was carried out in women pregnant for the fist time from the early stages of gestation (7-8 weeks); of these, 46 women were selected for whom the pregnancy was complicated by preeclampsia and who formed the following clinical groups: the 1 st group - 32 pregnant women with mild preeclampsia; the 2nd group - 14 pregnant women with severe preeclampsia. The control group - 48 somatically healthy pregnant women with the physiological course of pregnancy. In the serum of pregnant clinical observation groups in the 1 st (10-14 weeks), in the 2nd (23-26 weeks) and in the 3rd trimesters (32-35 weeks), the concentration of adrenocorticotropic hormone, β-endorphin was determined by ELISA , cortisol, insulin, placental lactogen, human chorionic gonadotropin, α-fetoprotein; the concentration of lymphocytes and markers of their activation (CD3, CD4, CD8, CD14, CD16, CD19, CD25, CD71, CD95, HLA DR) was determined by the immunoflorescence method using monoclonal antibodies. Results. For the women with the preeclampsia of the 1 st degree the neuroendocrinal regulation of homeostasis is broken in the 1 st trimester of pregnancy with creation of primary placental insuffiency, oppression of the stress-realizing function of the hypothalamo-pituitary system, development of insulin resistance, that as a whole testifis about dysadaptation of an organism of the women in the 1 st trimester of pregnancy. In the 1 st trimester the state of the fetoplacental complex for the pregnant women with preeclampsia, regardless of the degree of severity, is characterized by the dysbalance of hormones production, which testifis to development of primary placental insuffiency. Conclusions. For the women with preeclampsia of mild degree dysbalance of the immune system develops already in the 1 st trimester of pregnancy as relative augmentation of total of T-lymphocytes with simultaneous decrease of their functional activity, particularly Т-helpers of the 2nd type, which is accompanied by the decrease of anti-inflmmatory cytokines production. For the women with preeclampsia of serious degree the quantitative parameters of non-specifi and cellular immunity (CD3, CD4, CD8, CD16, HLA-DR) are reduced already in 1 st trimester of pregnancy with simultaneous rising of the value of immunoregulatory index (CD4/CD8) and functional activity of Т-helpers of the 1 st type on the background of the activity oppression of the 2nd type Т-helpers.